Etika Anti Korupsi dan Integritas Kehidupan Politik - Ernita, Tiara; Suyato, Suyato; Sari, Yunita (Jayapangus Press, 2025)
The decline in integrity in Indonesian political practice has created a moral crisis, resulting in diminished public trust in government institutions. This suggests that corruption and unethical behavior are not merely legal issues but also moral and spiritual challenges reflecting a low level of ethical awareness among political leaders. This study aims to explore the concepts of anti-corruption ethics and political integrity from the perspectives of moral philosophy and religious ethics, highlighting how moral principles can be integrated into political structures. Using a descriptive qualitative approach using a literature review, this study identified and analyzed literature related to political ethics and moral-religious writings. The study's findings suggest that political integrity based on anti-corruption moral and spiritual principles is crucial for ethical and just governance. Integrity in politics relies heavily on honesty, responsibility, and moral accountability.